Estudo teórico e numérico de absorvedores dinâmicos de vibrações ativos e adaptativos - Marques, Rodrigo França Alves (2000)
Dynamic Vibration Absorbers (DVAs) have been used to attenuate vibrations in various types of mechanical Systems. In its simplest form, a DVA is formed by an association of passive elements (inertia, stiffness and damping). The values of these parameters are selected so as to tune the DVA to a given value of the excitation frequency, assumed to be fixed. As a result, the attenuation capability of a passive DVA significantly decreases as the excitation frequency deviates from the nominal tuning frequency. To avoid this drawback, active and adaptive DVAs have been extensively studied lately, in an attempt to achieve larger effective bandwidths and self tunning capability. Active DVAs contain, besides the passive elements, an actuator wich applies a control force determined by an appropriate control law. Adaptive DVAs are understood as those constructed in such a way that the values of their physical parameters can be adjusted according to well-defined laws. In this work, some configurations of active and adaptive DVAs are assessed, namely: a) an active DVA using as feedback signal the time-delayed displacement response of the reactive mass (delayed resonator); b) a novel active DVA using a control law in wich the control force is expressed as a linear combination of the displacement, velocity and acceleration of the reactive mass, relative to the primary mass; c) an active DVA exploring linear quadratic optimal control theory; d) a vibrating string-type adaptive DVA; e) a pendulum-type adaptive DVA; f) an adaptive DVA formed from a beam with piezoelectric patches. For each configuration the theoretical foundations are first developed. Then, numerical applications are presented to assess their main features and performance.